2004
DOI: 10.1021/tx049904e
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Binding to the Chelation Therapy Agents DMSA and DMPS and the Rational Design of Custom Chelators for Mercury

Abstract: Clinical chelation therapy of mercury poisoning generally uses one or both of two drugs--meso-dimercaptosuccinic acid (DMSA) and dimercaptopropanesulfonic acid (DMPS), commercially sold as Chemet and Dimaval, respectively. We have used a combination of mercury L(III)-edge X-ray absorption spectroscopy and density functional theory calculations to investigate the chemistry of interaction of mercuric ions with each of these chelation therapy drugs. We show that neither DMSA nor DMPS forms a true chelate complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 25 publications
6
86
0
Order By: Relevance
“…However, several studies have shown that stable DMPS S-and DMSA S-conjugates of Hg 2ϩ are formed by a single mercuric ion bonding to the vicinal thiol groups on a single molecule of DMPS and DMSA, respectively (Rivera et al, 1989;Aposhian and Aposhian, 1990;Maiorino et al, 1991;Aposhian et al, 1995;Ruprecht, 1997). In contrast, George et al (2004) argue that at least two molecules of DMPS or DMSA and two atoms of Hg 2ϩ are required to form respective DMPS S-or DMSA S-conjugates of Hg 2ϩ . Regardless of the exact species of the complexes formed intracellularly, the findings from the current study and those of other studies show clearly that DMPS and DMSA are each capable of effectively reducing the renal and body burden of Hg 2ϩ (Planas-Bohne, 1981;Aposhian, 1983;Aposhian et al, 1992;Zalups et al, 1992;Ruprecht, 1997).…”
Section: Discussionmentioning
confidence: 88%
“…However, several studies have shown that stable DMPS S-and DMSA S-conjugates of Hg 2ϩ are formed by a single mercuric ion bonding to the vicinal thiol groups on a single molecule of DMPS and DMSA, respectively (Rivera et al, 1989;Aposhian and Aposhian, 1990;Maiorino et al, 1991;Aposhian et al, 1995;Ruprecht, 1997). In contrast, George et al (2004) argue that at least two molecules of DMPS or DMSA and two atoms of Hg 2ϩ are required to form respective DMPS S-or DMSA S-conjugates of Hg 2ϩ . Regardless of the exact species of the complexes formed intracellularly, the findings from the current study and those of other studies show clearly that DMPS and DMSA are each capable of effectively reducing the renal and body burden of Hg 2ϩ (Planas-Bohne, 1981;Aposhian, 1983;Aposhian et al, 1992;Zalups et al, 1992;Ruprecht, 1997).…”
Section: Discussionmentioning
confidence: 88%
“…The method is equally applicable to the study of other elements of concern, such as arsenic, selenium, thallium and lead. The technique also provides an ideal tool for investigating drugs such as chelation agents (34) and can be applied to the study of essential metals and other elements of interest during normal development.…”
Section: Resultsmentioning
confidence: 99%
“…The weaker binding of DMPS and DMSA is due to the fact there is not enough stereo-chemical space between the two thiols located on adjacent carbons to allow for binding a mercury atom. Therefore, DMPS and DMSA are not true chelators as they form "sandwich complexes" with two DMPSs forming single bonds each to a single Hg 2+ (George, et al 2004). Additionally, DMPS and DMSA chelates of Hg 2+ are negatively charged and do not effectively enter cells and are rapidly cleared by the kidney with little mercury exiting through the liver into the feces.…”
Section: Introductionmentioning
confidence: 99%